Comet assay to evaluate chromosomal changes in chickens (Gallus gallus domesticus) contaminated by lead in a city in Bahia - J. T. Braga-Neto; S. O. Tozetto; F. S. Oliveira; T. A. Conceição; W. P. C. Santos; M. S. Fernandes; M. D. Baliza (Brazilian Journal of Biology, 2023)
Abstract Chicken (Gallus gallus domesticus) is one of the primary sources of animal protein for the Brazilian population. Thus, the safety of this food is highly relevant. This study was based on the evidence of severe contamination of these animals by metals such as lead in Santo Amaro, Bahia. This exploratory study aimed to evaluate associations between lead levels in blood of chicken exposed to a contaminated area with the occurrence of chromosomal alterations, evidencing genotoxic effects. Serum lead analysis was performed by GF-AAS after dilution with a matrix modifier solution (Triton X-100 0.2% v/v and HNO3 0.1% v/v), while chromosomal damage was evaluated using the comet assay. The results showed genotoxic effects (positive comet assay) only for the specimen sample with higher serum lead concentrations (33.9 µg dL-1), suggesting the occurrence of toxic effects at this level of exposure. This work evaluated a relationship between the reduction of serum lead levels in chicken and increased distance from the primary polluting source - a lead processing plant (COBRAC). It also showed that lead is bioavailable in this territory, contaminating chicken and causing genotoxic effects in these animals, further expanding the concern with the local biota and the health of the residents of Santo Amaro.